Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s13063-021-05644-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimands in published protocols of randomised trials: urgent improvement needed

Abstract: Background An estimand is a precise description of the treatment effect to be estimated from a trial (the question) and is distinct from the methods of statistical analysis (how the question is to be answered). The potential use of estimands to improve trial research and reporting has been underpinned by the recent publication of the ICH E9(R1) Addendum on the use of estimands in clinical trials in 2019. We set out to assess how well estimands are described in published trial protocols. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…16 A standardised and piloted form was used for data extraction, which was conducted in duplicate by experienced trial statisticians using similar methods used in a recent review of estimands in protocols. 17 We only included articles from six high impact medical journals, all of which follow the CONSORT statement, so we may have found worse reporting around estimands had we included a wider range of journals that did not endorse CONSORT. However, previous research indicates that despite journal endorsement of reporting guidelines, reporting might still be suboptimal.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 A standardised and piloted form was used for data extraction, which was conducted in duplicate by experienced trial statisticians using similar methods used in a recent review of estimands in protocols. 17 We only included articles from six high impact medical journals, all of which follow the CONSORT statement, so we may have found worse reporting around estimands had we included a wider range of journals that did not endorse CONSORT. However, previous research indicates that despite journal endorsement of reporting guidelines, reporting might still be suboptimal.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…39 However, this review found that some trials defined their estimands in their protocol, which differs from a recent review of protocols published in October 2020 in Trials and BMJ Open, where no protocols explicitly defined the estimand, and estimands could be inferred in only 26% of protocols. 17 Use of estimands in this review might have been higher as we considered the six leading general medical journals and non-published protocols submitted as supplementary material.…”
Section: Research In Contextmentioning
confidence: 99%
“…As the ICH E9 (R1) guidance has been discussed in detail elsewhere, [4][5][6][7][8][9][10][11][12] our focus is on explaining-through contrasting examples-how researchers can effectively use estimands in their trial planning, design and analysis process to ensure clinical questions are precisely specified and the chance of a successful trial is maximised. In so doing, we hope to convert readers from estimand sceptics to enthusiasts.…”
Section: The Estimand Frameworkmentioning
confidence: 99%
“…The recent ICH-E9(R1) addendum on estimands 7 provides a strategy to systematically think through the trial objectives and ensure study methods are aligned to the objectives. To achieve a precise definition of the treatment effect the trial aims to estimate, the estimand defines five components [7][8][9][10][11][12][13][14][15] : (i) population; (ii) treatment condition(s) of interest; (iii) outcome measure; (iv) population-level summary (ie, how outcomes under different treatment conditions are to be compared); and (v) how intercurrent events, such as treatment discontinuation or switching, are to be handled.…”
Section: Introductionmentioning
confidence: 99%